Predictive factors for readmission due to neonatal hyperbilirubinemia: A retrospective case-control study. - Yueju Cai; Xiaolan Li; Ping Wang; Yanyan Song (PLoS ONE)
Objective Hyperbilirubinemia is a common cause of hospital readmission among neonates, but the factors contributing to post-discharge readmission remain unclear. Our study aimed to identify predictive factors associated with readmission for neonatal hyperbilirubinemia. Methods This retrospective case-control study included 421 neonates born at ≥ 35 weeks of gestation with hyperbilirubinemia between January and December 2021. The neonates were divided into a readmission group and a control group, and logistic regression was used to identify predictive factors associated with readmission. Results Among the 421 neonates studied, 32 (7.6%) were readmitted. Logistic regression analysis identified preterm birth (<37 weeks), ABO hemolysis, Glucose-6-Phosphate Dehydrogenase (G6PD) deficiency, and Total Serum Bilirubin (TSB) level at discharge as significant predictive factors for readmission due to hyperbilirubinemia in newborns. Additionally, a decrease in birth weight was significantly linked to an increased risk of readmission (OR = 0.998, P = 0.013), although the effect size was relatively small. Conclusions Prolonging hospitalization and implementing robust post-discharge monitoring may be essential for neonates with prematurity, ABO hemolysis, G6PD deficiency, or elevated TSB levels at discharge.